Evaluating TNA stability under simulated physiological conditions. Issue 10 (15th May 2016) - Culbertson, Michelle C.; Temburnikar, Kartik W.; Sau, Sujay P.; Liao, Jen-Yu; Bala, Saikat; Chaput, John C.
Graphical abstract: Abstract: Chemically modified oligonucleotides are routinely used as diagnostic and therapeutic agents due to their enhanced biological stability relative to natural DNA and RNA. Here, we examine the biological stability of α-l -threofuranosyl nucleic acid (TNA), an artificial genetic polymer composed of repeating units of α-l -threofuranosyl sugars linked by 2′, 3′-phosphodiester bonds. We show that TNA remains undigested after 7 days of incubation in the presence of either 50% human serum or human liver microsomes and is stable against snake venom phosphordiesterase (a highly active 3′ exonuclease). We further show that TNA will protect internal DNA residues from nuclease digestion and shield complementary RNA strands from RNA degrading enzymes. Together, these results demonstrate that TNA is an RNA analogue with high biological stability.